Weed coexistence in carioca bean inoculated with Rhizobium tropici or nitrogen-fertilized - Franciscon, Hugo; Costa, Neumárcio Vilanova da; Franciscon, Priscila Weber; Vasconcelos, Edmar Soares de; Egewarth, Vanessa Aline (Semina: Ciências Agrárias, 2022)
The supply of nitrogen (N) to the carioca bean plant via inoculation with Rhizobium tropici can prevent competition with the weed community by allowing the crop to absorb the nutrient available in the soil. On this basis, this study proposes to examine the period before weed interference (PBI) in the carioca bean plant following inoculation with R. tropici or N topdressing. The experiments were carried out under field conditions during the summer seasons of 2014 and 2015. A randomized-block experimental design with four replicates was adopted, in a 2 Ã— 11 factorial arrangement (common bean plant inoculated or topdressed with N Ã— 11 periods of coexistence with weeds, namely, 0, 7, 14, 21, 28, 35, 42, 49, 56, 63, or 90 days after emergence [DAE]). Nitrogen topdressing increased the crop's tolerance to coexist with weeds from 6 to 14 DAE, compared with inoculation with R. tropici The PBI for the inoculated common bean plant was 24 and 16 DAE in the years 2014 and 2015, respectively. For the N-topdressed plant, the PBI was 30 DAE in both years.